TINDAK TUTUR ASERTIF PIDATO PRESIDEN MOON JAE IN PADA KTT ANTAR KOREA 2018 SEBAGAI REPRESENTASI DIPLOMASI KOREA SELATAN TERHADAP KOREA UTARA - Rizka Adlina Veriza, - (2020)
This research is a descriptive qualitative research which has a purpose to uncover the diplomatic representation of South Korea towards North Korea by using the study of assertive speech-act. The data of this research are speech videos of president Moon Jae In taken from YouTube with its transcription and were carefully examined using speech-act clasification that was suggested by Searle (1969) and Korean assertive speech-act verb clasification proposed by Jang (1987). Two international relations experts were also interviewed to strengthen the representation data in terms of its political implication. The result of this research shows that the assertive speech-act dominates in President Moon Jae In's speech. The assertive verb of합의하다 habeuihada 'agreeing' (21%) is the most frequent verb that appears in the speech of Moon Jae In, followed by확인하다hwaginhada 'confirming', 밝히다balkhida 'stating' (15,7%) and논의하다non-euihada 'discussing' (10,5%). Based on the result of the interviews with international relations experts, the assertive speech acts of President Moon Jae In do represent the diplomatic state and attitude of the two Koreas, the benefits and the losses, as well as the influence of United States of America in the diplomacy done by South Korea towards North Korea.